Temporal dynamics of content communication - López-López, Wilson; Pontificia Universidad Javeriana (2013)
Scientometrics has experienced exponential growth in terms of number of papers submitted to area journals, and has also become a permanent source for advice and strategic decision-making for researchers, policy-makers, research managers and others. However, the most relevant effect may be the number of indicators that have been developed in order to account for the dynamics of research communication and the output of academic communities. At the same time, validity and utility of indicators have increased in societies both in the first and third worlds, an issue that has been dealt with in several editorials in Universitas Psychologica, given that our communities can be affected by the way knowledge is used, communicated and applied. It is not a coincidence that this discussion has also been taken to high impact journals (Science, Nature, Neuron), where it has met both favourable and unfavourable reactions. Some of these indicators are associated to how research communities use publications. Specifically, times and publication schedules have become relevant indicators, especially in Latin America, a region that has experienced tremendous growth in article output in all areas, more so than any other region. This growth allows us to analyse indicators to compare Latin America to other regions or country-to-country comparisons, controlling for similar socioeconomic conditions, such as investment, education, skills and relationships, and also knowledge and information infrastructures. The development of these measurements has been high enough that new indicators have been proposed to predict the potential impact of a new publication. This would show that interpretation of these indicators is complex and involves more relevant, less local information. It is clear, however, that some of these indicators are important, especially those related to publication schedules. The temporal dimension is more important today than ever due to institutional demands, knowledge obsolescence and the need for cooperation networks, but also because of the growing awareness that results should be made available quickly. This is why preprint articles and DOI (Digital Object Identifiers) will be included in Universitas Psychologica from this issue (volume 12, issue 3, 2013), to promote faster citation. We expect to enter a new development phase by making papers available before the print edition. This alternative follows a worldwide publication trend, and shows that our emergent academic communities have started to create, communicate and appreciate their own knowledge. This may be why the hegemony of traditional impact indicators has been questioned. We have also noticed, upon analysing tables of most-read and most-downloaded articles in our journal, that it is articles from the past few years that have a higher download rate, which suggests a clear trend in the use of knowledge. The growth experienced by our journal and its inclusion in the first quartiles in large information systems have involved changes and challenges, in terms of quality, quantity and prestige. This is why we feel to need to point out that we are constantly in a path towards advancement and we expect to be able to add new features to the website, in our quest for shorter publication times and higher quality of contents.